WAYS TO SHOW VIRTUAL EXHIBITIONS (Web of Teachers: Inderscience Research, 2024)
Since the advent of informatics and information technology, computers and electronic devices, new solutions have been proposed to analyze, store, and distribute data in them. As these technologies have advanced, we have also produced innovations in the display of Vertual exhibitions, and we try to highlight these innovations in this article